Pandas in one hour : showcasing the high-level features of the Pandas library. (Manning Publications, 2020)
The author of "Pandas in Action" introduces the high-level features of the Pandas library and showcases how it can help expand your data analysis operations. You will be presented with many examples of why Pandas library is called 'Excel on steroids.'.